Concurrent Assessment of Deformability and Adhesiveness of Sickle Red Blood Cells by Measuring Perfusion of an Adhesive Artificial Microvascular Network - Lu, Madeleine; Kanne, Celeste K.; Reddington, Riley C.; Lezzar, Dalia L.; Sheehan, Vivien A.; Shevkoplyas, Sergey S. (Frontiers in Physiology, 2021)
Biomarker development is a key clinical research need in sickle cell disease (SCD). Hemorheological parameters are excellent candidates as abnormal red blood cell (RBC) rheology plays a critical role in SCD pathophysiology. Here we describe a microfluidic device capable of evaluating RBC deformability and adhesiveness concurrently, by measuring their effect on perfusion of an artificial microvascular network (AMVN) that combines microchannels small enough to require RBC deformation, and laminin (LN) coating on channel walls to model intravascular adhesion. Each AMVN device consists of three identical capillary networks, which can be coated with LN (adhesive) or left uncoated (non-adhesive) independently. The perfusion rate for sickle RBCs in the LN-coated networks (0.18 ± 0.02 nL/s) was significantly slower than in non-adhesive networks (0.20 ± 0.02 nL/s), and both were significantly slower than the perfusion rate for normal RBCs in the LN-coated networks (0.22 ± 0.01 nL/s). Importantly, there was no overlap between the ranges of perfusion rates obtained for sickle and normal RBC samples in the LN-coated networks. Interestingly, treatment with poloxamer 188 decreased the perfusion rate for sickle RBCs in LN-coated networks in a dose-dependent manner, contrary to previous studies with conventional assays, but in agreement with the latest clinical trial which showed no clinical benefit. Overall, these findings suggest the potential utility of the adhesive AMVN device for evaluating the effect of novel curative and palliative therapies on the hemorheological status of SCD patients during clinical trials and in post-market clinical practice.